The Effect of Liquid Organic Fertilizer (LOF) Banana on The Growth and Yield of Purple String Bean (Vigna Unguiculata. L.) - Aisyah; Inti Mulyo Arti; Duta, Orion Jaga (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The utilization of organic waste as a base material for liquid fertilizer production is gaining popularity due to its environmental friendliness and potential to enhance crop productivity. Banana waste is one type of organic material that can be processed into liquid fertilizer containing nutrients beneficial for plant growth. This study aimed to evaluate the effect of applying liquid organic fertilizer (LOF) derived from banana waste on the growth and yield of long bean (Vigna unguiculata). The experiment was conducted at UG Technopark, Jamali Village, Cianjur, West Java, from March to June 2024, using a Completely Randomized Block Design (RCBD) with a single factor, namely the concentration of banana POC, consisting of four levels: 0 ml/L (P0), 10 ml/L (P1), 20 ml/L (P2), and 30 ml/L (P3). The observed parameters included the number of leaves, stem diameter, plant height, pod fresh weight, pod length, number of pods, and flowering age. The results showed that the application of banana LOF significantly affected the growth and yield of long beans, particularly the number of leaves, stem diameter, plant height, and number of pods. Increasing the concentration of banana LOF positively impacted the observed growth and yield parameters.